Impact of Focused Intraoperative Transthoracic Echocardiography by Anaesthesiologists on Management in Hemodynamically Unstable High-Risk Noncardiac Surgery Patients. Issue 4 (August 2017) - Kratz, T.; Steinfeldt, T.; Exner, M.; Dell'Orto, M. C.; Timmesfeld, N.; Kratz, C.; Skrodzki, M.; Wulf, H.; Zoremba, M.
Abstract : (Abstracted from J Cardiothorac Vasc Anesth, 31:602–609, 2017) Perioperative hemodynamic monitoring and intervention using transthoracic echocardiography (TTE) in high- risk surgery patients can decrease the rates of adverse events, morbidity, and mortality; however, evidence regarding its benefits is required. This prospective interventional study aimed at evaluating the efficacy of intraoperative TTE to alter patient management in high-risk and extensively monitored surgical patients susceptible to hemodynamic instability.